2003
DOI: 10.1038/sj.bjp.0705227
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of mdr1a expression in the brain and liver during CNS inflammation alters the in vivo disposition of digoxin

Abstract: 1 Inflammation is a pathophysiological event that has relevance for altered drug disposition in humans. Two functions of P-glycoprotein (P-gp) are hepatic drug elimination and prevention of drug entry into the central nervous system (CNS). Our objective was to investigate if localized CNS inflammation induced by Escherichia coli lipopolysaccharide (LPS) would modify mdr1a/P-gp expression and function in the brain and liver. 2 Our major finding was that the CNS inflammation in male rats produced a loss in the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
97
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(104 citation statements)
references
References 42 publications
7
97
0
Order By: Relevance
“…The mRNA levels of each transporter were examined by quantitative real-time PCR. Methods for RNA isolation, cDNA synthesis and real-time PCR have been previously described (Goralski et al, 2003;Teng and Piquette-Miller, 2005;Wang et al, 2005). Briefly, RNA was extracted from tissues by use of the QuickPrep total RNA extraction kit (Amersham, Piscataway, NJ), and singlestranded cDNA was synthesized from 2.5 g of RNA by use of the First Strand cDNA synthesis kit (MBI Fermentas, Hanover, MD) according to the manufacturer's protocol.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mRNA levels of each transporter were examined by quantitative real-time PCR. Methods for RNA isolation, cDNA synthesis and real-time PCR have been previously described (Goralski et al, 2003;Teng and Piquette-Miller, 2005;Wang et al, 2005). Briefly, RNA was extracted from tissues by use of the QuickPrep total RNA extraction kit (Amersham, Piscataway, NJ), and singlestranded cDNA was synthesized from 2.5 g of RNA by use of the First Strand cDNA synthesis kit (MBI Fermentas, Hanover, MD) according to the manufacturer's protocol.…”
Section: Methodsmentioning
confidence: 99%
“…Placental efflux transporters, such as Bcrp and Pgp, are believed to protect placental and fetal tissues by removing potentially toxic xenobiotics and endogenous metabolites. It has been previously demonstrated that endotoxin and other inflammatory stimuli impose a down-regulation of Pgp in epithelial tissues of the liver, intestine, brain, and placenta in rodents (Piquette-Miller et al, 1998;Hartmann et al, 2001;Goralski et al, 2003;Kalitsky-Szirtes et al, 2004;Wang et al, 2005). Recently, it has been reported that intestinal expression of BCRP is decreased in patients with ulcerative colitis (Englund et al, 2007); however, the effect of inflammation on the placental Bcrp expression is unknown.…”
Section: Effect Of Endotoxin On Placental Drug Transportersmentioning
confidence: 99%
“…Initially discovered in tumour cells while investigating the multidrug resistance mechanism, it has been also found and studied in many nontumour cells/tissues (Montano et al, 1996;Smit et al, 1998;Dautrey et al, 1999;Jonker et al, 1999;Gutmann et al, 2000;Florea et al, 2001;Batetta et al, 2003;Cisternino et al, 2003;Goralski et al, 2003;Elliott et al, 2004). P-gp indeed is involved in all pharmacokinetic events (Varma et al, 2003) and many single-nucleotide polymorphisms in the MDR1 gene have been correlated with differences in individual drug responsiveness (Marzolini et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Out of the 13 TLRs identified in mammals, TLR4 is activated by the gram-negative component, LPS, and TLR2 is activated by the gram-positive component, LTA (Aliprantis et al, 1999;Takeuchi et al, 1999). We and others have shown down-regulation of Cyp3a11 and P-gp in LPS sensitive TLR4 wild type (C3HeB/FeJ) mice could not be detected in TLR4-mutant (C3H/HeJ) mice (Ghose et al, 2008;Goralski et al, 2003;. Recent data from our lab showed that down-regulation of gene expression of key hepatic phase I and phase II DMEs in TLR2 +/+ mice by LTA was blocked in TLR2 -/-mice (Ghose et al, 2009).…”
Section: Mechanisms For Altered Drug Metabolism In Infections and Infmentioning
confidence: 91%